One Health: The Human-Animal-Environment Interfaces in Emerging Infectious Diseases Food Safety and Security, and International and National Plans for Implementation of One Health Activities - Mackenzie, John S.; Jeggo, Martyn.; Daszak, Peter.; Richt, Juergen A. (Current Topics in Microbiology and Immunology, 2013)
The second volume on One Health explains in detail how to implement three key aspects of the One Health paradigm food safety and security, national plans for a holistic one health approach, and relevant new technologies and approaches. The fourteen chapters, each by an internationally recognized authority, are organized into three sections of four or five chapters each, that break new ground in clarifying precisely how One Health can become an operational reality in local, national and international public health initiatives. Section three begins with an international overview on food safety and security. The importance of a One Heath approach is then explained in relation to four specific problems the growing prevalence of antibiotic resistance, bovine spongiform encephalopathy and pathogenic E.coli. Section four begins with the role of the Food and Agricultural Organization (FAO) in promoting One Health. The formulation and implementation of national plans for implementing the One Health paradigm are then set out for Africa, the Western Pacific, Southeast Asia and Mongolia. The final section of this two volume book is devoted to implementing new technologies and new approaches to One Health. A wide-ranging analysis considers the importance of climate change and a social-ecological systems approach, as well as how to operationalize One Health, how to move from emergency response to prevention at source, and how to implement an educational strategy that builds a foundation for One Health in emerging disease management.  It is anticipated that this two volume book will become a benchmark for practitioners of One Health, empowering a balanced multidisciplinary approach to the complexities of the human-animal-environment interface.